Bronchiectasis in African children: Challenges and barriers to care - Verwey, Charl; Gray, Diane M.; Dangor, Ziyaad; Ferrand, Rashida A.; Ayuk, Adaeze C.; Marangu, Diana; Kwarteng Owusu, Sandra; Mapani, Muntanga K.; Goga, Ameena; Masekela, Refiloe (Frontiers in Pediatrics, 2022)
Bronchiectasis (BE) is a chronic condition affecting the bronchial tree. It is characterized by the dilatation of large and medium-sized airways, secondary to damage of the underlying bronchial wall structural elements and accompanied by the clinical picture of recurrent or persistent cough. Despite an increased awareness of childhood BE, there is still a paucity of data on the epidemiology, pathophysiological phenotypes, diagnosis, management, and outcomes in Africa where the prevalence is mostly unmeasured, and likely to be higher than high-income countries. Diagnostic pathways and management principles have largely been extrapolated from approaches in adults and children in high-income countries or from data in children with cystic fibrosis. Here we provide an overview of paediatric BE in Africa, highlighting risk factors, diagnostic and management challenges, need for a global approach to addressing key research gaps, and recommendations for practitioners working in Africa.